PENYULUHAN PENINGKATAN PENGEMBANGAN MANAJEMEN SUMBER DAYA MANUSIA SERTA KUALITAS PELAYANAN UNTUK MENINGKATKAN PRODUKTIVITAS KARYAWAN - Jaya, Umban Adi; Priyana, Indarta; Albar, Fauzan Manafi; Hodijah, Cucu; Novitasari, Yuli (Jurnal Abdimas Bina Bangsa, 2025)
This service aims to improve the productivity of the Kuda Tandang Processed Snack Factory in Sumedang, through counseling and development of human resource (HR) management and service quality. This factory faces challenges in HR management and service standards that have a negative impact on productivity and competitiveness in an increasingly competitive market. This counseling applies a quantitative descriptive method with a survey and interview approach, involving 33 employees from various divisions. The counseling program includes HR management training and improving service quality. Data analysis uses questionnaires, interviews, and productivity reports before and after the counseling. The results of the study showed that this training program succeeded in improving employee technical and managerial skills, which ultimately increased productivity, product quality, and customer satisfaction. Short-term and long-term evaluations confirmed that improvements in HR and customer service contributed positively to the company's operational efficiency and competitiveness.